2014
DOI: 10.1136/heartjnl-2014-306472
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk profile and frailty in a population-based study of older British men

Abstract: BackgroundFrailty in older age is known to be associated with cardiovascular disease (CVD) risk. However, the extent to which frailty is associated with the CVD risk profile has been little studied. Our aim was to examine the associations of a range of cardiovascular risk factors with frailty and to assess whether these are independent of established CVD.MethodsCross-sectional study of a socially representative sample of 1622 surviving men aged 71–92 examined in 2010–2012 across 24 British towns, from a prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 25 publications
5
79
1
4
Order By: Relevance
“…Observational studies have demonstrated a significant association between frailty and cardiovascular morbidity and mortality [20,21]. A longitudinal study recently reported that pre-frailty diagnosed based on Fried's biological syndrome model criterion was also significantly associated with cardiovascular events [22].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have demonstrated a significant association between frailty and cardiovascular morbidity and mortality [20,21]. A longitudinal study recently reported that pre-frailty diagnosed based on Fried's biological syndrome model criterion was also significantly associated with cardiovascular events [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a British prospective study, the triglyceride levels were higher among frail (12%) and pre-frail individuals (9%) than among non-frail individuals (7%), which disagrees with the results from the present study. 7 In another study among elderly individuals, slight or moderate elevations in triglyceride and LDL levels were observed. 19 Consequently, occurrences of lipid problems, among others, are risk factors for arterial coronary disease, 36 which is related to frailty.…”
Section: Resultsmentioning
confidence: 93%
“…7 In Brazil, a study conducted in 17 cities found that BMI and abdominal circumference were associated with frailty, although obesity did not present any significant association. 8 Additionally, in a study among community-living elderly people, frailty was associated with higher blood pressure, larger abdominal circumference and low blood HDL levels.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…To further support this idea, another study done in 2015 supported frailty as an independent risk factor for various diseases along the CVD spectrum. A low HDL level was one of the parameters [50]. As a part of the Longitudinal Aging Study Amsterdam, it was described that a lower total cholesterol was related to a higher rate of decline on information-processing speed indicating, ultimately, that lower total cholesterol may be considered to be a marker of frailty and predictive of lower cognitive function in the elderly [51].…”
Section: Frailty and Lipidsmentioning
confidence: 99%